Dependence of ultrasound decorrelation on urine scatter particle concentration for a non‐invasive diagnosis of bladder outlet obstruction. Issue 8 (22nd September 2014) - Arif, Muhammad; Idzenga, Tim; de Korte, Chris L.; van Mastrigt, Ron
<x xml:space="preserve">Abstract</x> Aims To develop a non‐invasive method to diagnose Bladder Outlet Obstruction (BOO) based on decorrelation of subsequently acquired UltraSound (US) data of urinary flow, we studied the influence of scatter particle concentration on the decorrelation process in urethra models using both aqueous solutions of scattering particles and urine samples. Methods A tissue mimicking urethra model made from PolyVinyl Alcohol (PVA) solution was infused with seven aqueous solutions containing different particle concentrations at a constant flow rate value of 10 ml/sec. The average correlation coefficients between subsequent US images were calculated and plotted as a function of particle concentration. This procedure was also applied to stepwise diluted urine samples from nine healthy volunteers. An inversely exponential curve was fitted to the experimental data to estimate the scatter particle concentration in the urine samples. Results The average correlation values between subsequent US images increased with the particle concentration. The morning urine samples contained an appropriate number of scattering particles to make clinical application of the decorrelation method possible. The fitted correlation curves made an estimation of urine particle concentration possible. Conclusion The results of this study show that morning urine is suitable for US decorrelation without correcting for differences in particle concentration. Neurourol. Urodynam. 34:781–786, 2015. © 2014 Wiley Periodicals, Inc.